2003
DOI: 10.1074/jbc.m212334200
|View full text |Cite
|
Sign up to set email alerts
|

The Comparative Role of Activator Protein 1 and Smad Factors in the Regulation of Timp-1 and MMP-1 Gene Expression by Transforming Growth Factor-β1

Abstract: The balance between matrix metalloproteinases (MMPs) and their inhibitors, the tissue inhibitors of metalloproteinases (TIMPs), is pivotal in the remodeling of extracellular matrix. TGF-␤ has profound effects on extracellular matrix homeostasis, in part via its ability to alter this balance at the level of gene expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
179
1
5

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(196 citation statements)
references
References 50 publications
(53 reference statements)
9
179
1
5
Order By: Relevance
“…Wnt5a increased the promoter activity (Figure 5b). It was reported that the proximal AP-1 site at À72 is necessary for the phorbol ester-induced expression of MMP-1 (Hall et al, 2003). The basal reporter gene activity was decreased by introducing mutations in this area (AP-1 mut), and Wnt5a did not stimulate it (Figure 5b).…”
Section: Mechanism Of Wnt5a-induced Invasion By Pca Cellsmentioning
confidence: 90%
See 1 more Smart Citation
“…Wnt5a increased the promoter activity (Figure 5b). It was reported that the proximal AP-1 site at À72 is necessary for the phorbol ester-induced expression of MMP-1 (Hall et al, 2003). The basal reporter gene activity was decreased by introducing mutations in this area (AP-1 mut), and Wnt5a did not stimulate it (Figure 5b).…”
Section: Mechanism Of Wnt5a-induced Invasion By Pca Cellsmentioning
confidence: 90%
“…The MMP-1 promoter-luciferase constructs and pGEXaPAK-CRIB were provided by Dr I Clark (University of East Anglia, Norwich, UK) (Hall et al, 2003) and Dr K Kaibuchi (Nagoya University, Nagoya, Japan), respectively. DU145, LNCap and PC3 cells were obtained from American Type Culture Collection (Manassas, VA, USA) and were grown in RPMI-1640 medium supplemented with 10% fetal bovine serum.…”
Section: Materials and Chemicalsmentioning
confidence: 99%
“…In the murine TIMP-1 gene, the AP1 site is located at À59 bp and is important in both basal and inducible TIMP-1 gene expression. 21 Many cytokines and matricellular factors influence MMP/TIMP expression through the NF-kB and AP-1 pathways. 22 Stimulation of rat cardiac fibroblasts with Ang II induces the production of both NF-kB and AP-1 transcription factors and is associated with an increase in collagen I production as well as a decrease in MMP-1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…The phorbol myristate acetate (PMA) stimulates the expression and production of MMP-1 in human fibroblasts through the binding of the c-Jun factor to the AP-1 site of the MMP-1 promoter (25,26). Conversely, all-trans-or 9-cis-retinoic acid (RA) isomers reduce MMP-1 expression via the formation of a large repressor complex containing c-Jun that binds directly to the AP-1 site and apparently tethers the retinoid receptors (RARs and RXRs) to the complex (27).…”
Section: Mmp-1 Overexpression Is a Specific Trait Of Ttd/xp-d Dermal mentioning
confidence: 99%